Faulty towers: Reform, Radicalism and the Gothic Castle, 1760-1800 - Chiu, Frances (Romanticism on the Net, 2006)
AbstractWho has not been on an amusement park ride that proceeds through a haunted house, complete with cobwebs, coffins, once opulent furnishings, and a ghost or two? It is an idea that we have encountered countless times in novels and movies alike yet one that continues to mystify us. How did the trope of the haunted Gothic castle/mansion materialize so quickly in the late eighteenth century? Although we have more or less recognized Walpole’s castle of Otranto as its prototype, we are yet unacquainted with the rapid construction of the so-called “haunted castle/mansion/house” trope, particularly between 1777 and 1800. This essay contends that far from being accidental, the foundations of this trope were heavily impacted not only by populist histories that detailed the beginnings of Britain’s stately castles, abbeys, and houses and the dark tales of their presiding tyrants, but more significantly by the simultaneous campaigns for parliamentary reform and religious toleration. I demonstrate how historians began to identify the chief features of Gothic architecture as Norman during a period in which reformers and radicals were also beginning to revive the myth of the Norman Yoke and stir up resentment against the church and aristocracy. I also show how reformers were increasingly inclined to deploy architectural metaphors in their discussions of Britain’s political institutions and establishments: just as conservatives argued for the retention of the Gothic castle, progressives argued for its destruction, regarding it in some instances as either haunted or filled with harpies (i.e., Jeremy Bentham). Finally, I analyze the means by which Jacobin and Gothic novelists adopted the Gothic castle as a criticism of Britain’s so-called “establishments” and, more interestingly, came to explore the idea of identification between villains and their dark abodes in their novels.